(3MjdI GdChdjGA hWHbI GdCUajGAs - (3CMeO Hf YHO Gddg Hf CMeO GdCUHgGfj, CHh fYje, J (B430 (3g` s ((3eMeO UGOb Hf GdSjO Cejf GdeGdM s)
(3ChdgG (B:s
(3MOKfG SdjeGf Hf CMeO Yf eLGgO bGd eG ef jhe jfbV ef GdOfjG GdGbGd Pdc Gdjhe GdMeO ddg GdPi GQGVi ef GdOfjG hCgdgG s
(3BNQgG (B:s
(3MOKfG eMeO Hf LYaQ bGd MOKfG LYaQ GdUGjZ bGd MOKfG bHjUI GHf YbHI hgh ai GdLRA GdPi jdjg s
(3Vef eLehY , JQJjHgG (B: (3GdKGdKs
(3GfXQg eY GdeNWhW Qbe (B183 (3ef faS GdHYKIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B157 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B282s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(3 / 5294) s
Keywords: (3GdJGQjNs